Muscle growth and anabolism in intensive care survivors (GAINS 2.0): Protocol for a multi-centre randomised; placebo controlled clinical trial of nandrolone in deconditioned adults recovering from critical illness. - Matthew Anstey; Ed Litton; Maryam Habibi; Lisa Van der Lee; Robert Palmer; Natalie Tran; Bianca Mammana; Stacey Scheepers; Annamaria Palermo; Xavier Fiorilla; Bhaumik Mevavala; Adrian Regli; et al. (PLoS ONE)
Background Intensive care patients can experience significant long-term impairment in mobility and function caused by their critical illness. A potential contributory factor apart from critical illness polymyoneuropathy is the low levels of anabolic hormones in these patients. Testosterone levels in critically ill patients are extremely low, even in the latter recovery phase. A potential solution to critical illness myopathy may be to provide anabolic support in addition to standard care (early physiotherapy) to further improve gains in strength. Research question This project aims to test whether a synthetic testosterone (nandrolone) improves muscle strength in ICU survivors compared to placebo. Methods GAINS 2.0 is a multicentre, randomised, double blinded placebo-controlled trial which will allocate ICU patients in a 1:1 ratio to nandrolone compared to placebo which commenced recruitment in July 2023. Adult patients admitted to the ICU, receiving nutrition for a minimum of 24 hours with an ICU stay of at least 5 days, or patients with significant weakness as result of their ICU stay (such that they are unable to mobilise independently) will be eligible to participate. Sample size will be 54 patients. Patients will be randomised to receive nandrolone 100mg (males) / 50mg(females) weekly for 3 weeks in addition to standard care. The co-primary outcomes are the time to walking with one person assisting (Intensive Care Mobility scale = 8 or more, in days from randomisation), change in muscle strength measured by the Medical Research Council (MRC) muscle strength sum score from enrolment to hospital discharge and number of days out of hospital up to day 90 post-discharge. Secondary outcomes are grip strength measured by hand-held dynamometry. SF-36 scores (quality of life and functional domains), and days to return to work, for those working pre-ICU, will be collected via a 3-month phone follow-up. Conclusions A previous pilot feasibility trial showed that nandrolone is safe and feasible. We hypothesize nandrolone will improve muscle strength and physical functioning at hospital discharge and at follow-up. The results of this trial may have significant interest to clinicians and patients considering the large and increasing number of patients surviving intensive care but with physical impairment. This trial may have significant implications on lowering hospital costs and daily adjusted life years. Trial registry anzctr.org.au; No.: ACTRN12623000729628 URL: anzctr.org.au.